Design, synthesis and anticancer activity of constrained sphingolipid-phenoxazine/phenothiazine hybrid constructs targeting protein phosphatase 2A. Issue 18 (15th September 2019) - Garsi, Jean-Baptiste; Vece, Vito; Sernissi, Lorenzo; Auger-Morin, Catherine; Hanessian, Stephen; McCracken, Alison N.; Selwan, Elizabeth; Ramirez, Cuauhtemoc; Dahal, Amogha; Romdhane, Nadine Ben; Finicle, Brendan T.; Edinger, Aimee L.
Graphical abstract: Abstract: Inspired by the cytotoxicity of perphenazine toward cancer cells and its ability to activate the serine/threonine protein phosphatase 2A (PP2A), we prepared series of ether-carbon linked analogs of a constrained synthetic sphingolipid analog 3, known for its cytotoxicity, nutrient transporter down-regulation and vacuolation properties, incorporating the tricyclic neuroleptics phenoxazine and phenothiazine to represent hybrid structures with possible synergistic cytotoxic activity. While the original activity of the lead compound 3 was diminished by fusion with the phenoxazine or phenothiazine tethered moieties, the corresponding 3-pyridyltetryl ether analog 10 showed cytotoxicity and nutrient transporter down-regulation similar to the lead compound 3, although it separated these PP2A-dependent phenotypes from that of vacuolation.